Quo Vadis Pengembangan Keilmuan UIN: Sekularisasi atau Quranisasi Ilmu Pengetahuan - Lukman Hakim (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Abstract: The conversion of State Islamic Institute to State Islamic University triggers  debate among intellectuals. Supporters of the conversion see the effort a way to islamize  knowledge. While the opponents see it differently, the conversion would secularize  knowledge. Starting from this point, this article closely studies the efforts of the Islamic  University in developing the knowledge, would it be directed to either secularization or  islamization one? To respond the question, this article offers as well as formulates the  blueprint of modified knowledge development at the Islamic University that is based on the  Quran. The blueprint is formulated through three main stages. Firstly, it positions Tauhid to be the foundation of the knowledge. Secondly, it formulates integrating curriculum that is  based on Islamic knowledge and sciences. Lastly, it revitalizes the value of practicality into  Islamic knowledge. The modified blueprint is expected to strengthen Islamic science that is  based on the true Tauhid. At the same time, it offers responsibility in responding the future  challenges.Abstrak: Transformasi status Institut Agama Islam Negeri menjadi Universitas Islam  Negeri memunculkan pro dan kontra di kalangan intelektual. Intelektual yang pro dengan  optimis memandang perubahan ini sebagai peluang islamisasi ilmu pengetahuan.  Sedangkan kalangan yang kontra menilainya sebagai bagian dari upaya sekularisasi ilmu- ilmu keislaman. Berangkat dari pertentangan pendapat di atas maka makalah ini ingin  mencermati ke mana arah pengembangan keilmuan UIN ini hendak dibawa? Apakah ia  akan mengarah kepada sekularisasi ilmu pengetahuan atau sebaliknya akan terjadi  qur‟anisasi ilmu pengetahuan? Untuk menjawab permasalahan di atas maka tulisan ini  menarwarkan sekaligus memformulasikan rekayasa blue print pengembangan keilmuan  UIN yang berbasis qur‟ani. Perancangan ini diformulasikan dalam tiga tahapan utama;  meletakkan landasan keilmuan berbasis tauhid, memformulasikan kurikulum yang  mengintergrasikan ilmu-ilmu keislaman dengan ilmu-ilmu umum, dan merevitalisasikan  nilai-nilai praktis dalam pengembangan ilmu-ilmu keislaman. Rekayasa blueprint ini  diharapkan menjadi formula penguatan sains Islam ke depan dengan landasan tauhid yang  benar sekaligus memiliki responsibilitas dalam menjawab tantangan masa depan.